(untitled) (GEOgraphia, 2010)
Este artigo objetivo analisar a gênese e impactos da hidrovia do Madeira sob a égide do Grupo André Maggi, uma das maiores corporações do agronegócio no Brasil. Em linhas gerais, a hidrovia possibilitou a subordinação da renda do produtor, expansão da lavoura de soja em direção à Amazônia, impactos socioambientais e corporatização de parcelas da Chapada dos Parecis sob a ação do Grupo André Maggi através do financiamento e comercialização da produção de grãos. Abstract This article aims to analyze the impacts of the Madeira watenvay, controlled by Andre Maggi Group, one of the largest agribusiness corporation in Brazil. In general, the watenvay made possible the subordination of the producer’s income, the expansion of soybean crops towards the Amazonia, social impacts and land control in part of the Chapada of the Parecis under the action of the Andre Maggi Group through the financing and cornmercialization of the grain production.